2015
DOI: 10.1089/jwh.2015.5251
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Vaccine Uptake After a Tailored, Online Educational Intervention for Female University Students: A Randomized Controlled Trial

Abstract: We found that an individually tailored, online educational tool had similar effects as a nontailored factsheet on HPV-related knowledge, intention to HPV undergo vaccination, and HPV vaccine uptake among previously unvaccinated female university students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 23 publications
3
71
1
Order By: Relevance
“…However, the present findings revealed that those effects wore off during the 4 months following intervention. Our results are consistent with those of a previous study showing that risk perception, intention to be vaccinated, and HPV vaccine uptake did not differ significantly between baseline and 3 months following intervention among female university students in the United States [10].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the present findings revealed that those effects wore off during the 4 months following intervention. Our results are consistent with those of a previous study showing that risk perception, intention to be vaccinated, and HPV vaccine uptake did not differ significantly between baseline and 3 months following intervention among female university students in the United States [10].…”
Section: Discussionsupporting
confidence: 92%
“…The long-term effects of messages should be investigated because HPV vaccination expects multiple injections given over a series of weeks: in Japan, the second dose is given 1 month after and the third dose is given 6 months after the first dose. One previous study examined the impact of an individually tailored intervention on knowledge, risk perception, intention to be vaccinated, and uptake regarding HPV vaccine, among unvaccinated female university students over 3 months following the intervention [10]. However, no studies have examined the long-term effects of intervention among parents of adolescent daughters.…”
Section: Introductionmentioning
confidence: 99%
“…While these two studies were successful in increasing interest in vaccination and willingness to vaccinate, other attempts have been less successful. An online intervention called “MeFirst” incorporated college students’ baseline knowledge of HPV in order to design a tailored educational intervention; however, 3 months after the intervention, those randomized to the tailored education were no more likely to have initiated the vaccine series than those who had just read the CDC information face-sheet ( 54 ). Of note, few studies evaluate actual vaccination uptake outcomes, and most rely on changes in reported intention to vaccinate as a surrogate, which may over-estimate the impact of education on vaccination rates.…”
Section: Interventions To Improve Delivery Of the Hpv Vaccinementioning
confidence: 99%
“…To date, only few tailored interventions to encourage HPV vaccination have been tested [ 10 - 13 ]. Three of these showed positive results.…”
Section: Introductionmentioning
confidence: 99%